Corrosion of twin belt and twin roll cast AlMg3Mn alloys. (May 2014) - Birol, F.; Birol, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Corrosion of twin belt and twin roll cast AlMg3Mn sheet samples was investigated. The AlMg3Mn sheet samples submitted to immersion tests undergo alkaline pitting around Al–Fe and αc-Al(Fe, Mn)Si intermetallic particles in the twin roll and twin belt cast samples respectively. The weight loss is higher in the latter and increases with increasing homogenisation temperature for both groups. The twin roll cast AlMg3Mn samples reveal very few and small alkaline corrosion pits and hence much less weight loss in the immersion tests. The pitting activity is governed in the immersion tests by the microgalvanic corrosion activities between the intermetallic particles and the matrix while the anodic particles were inactive.